An evaluation of the somatosensory profile of hemiparetic individuals - R.S. Mota; T.M.A. Conceição; T.M.C. Soares; I. Lima e Silva; F.B. Cardoso; H. Beresford (Desafio Singular, 2010)
The purpose of this study was to evaluate the somatosensory profile of 18 hemiparetic spastic victims of stroke with and without blocking vision. Maximal isometric contraction test was used for flexor and extensor muscles of the hip and knee, and flexor plantar muscles. The number of cycles per minute on stationary bike was also measured with eyes opened and closed. Significant differences were found suggesting the existence of miscommunication between sensory-motor neural mechanisms responsible for voluntary motor actions in these individuals.